Investigating Determinants of Industry–University Collaboration in an Open Innovation Context: Comparative Evidence from an Exploratory Study. (November 2021) - Baban, Calin Florin; Baban, Marius; Rangone, Adalberto
In an open innovation (OI) paradigm, universities are considered as important sources of external scientific knowledge for industry, and comparative study of such collaboration can result in more effective and efficient employment of OI. Within this framework, this study explores how the determinants of collaboration between industry and universities in an open context of innovation are addressed by firms within industrial areas. For this purpose, a conceptual framework of industry–university determinants in an open context of innovation is developed from the related literature. Taking into consideration the determinants integrated into the framework, this study compares motives, barriers, channels of knowledge transfer, benefits and drawbacks of such collaboration in two Italian and Romanian industrial areas. Comparative differences in each OI determinant between the firms from the two Italian and Romanian industrial areas are analysed. The associations among the study determinants are also investigated based on correlation matrices among the five determinants in both Italian and Romanian firms. An artificial intelligence approach based on fuzzy logic was developed to predict the impact of the study determinants on the perception of universities as a source for OI activities of firms.